Metacognitive Listening Strategies and Critical Listening Attitudes as Predictors of Teacher Candidates' Academic Listening Skills: A Structural Equation Modeling Analysis - Polatcan, Faruk; Bicer, Nursat; Er, Onur (Sage Publications Inc, 2025)
The objective of this study is to ascertain the relative influences and predictive relationships between metacognitive listening strategies, critical listening attitudes and academic listening skills of Turkish teacher candidates. In consideration of the ease of accessibility and economic factors, the participants were selected through the utilization of the convenience sampling method, which is appropriate when the aim is to obtain a representative sample from an accessible population. A total of 223 teacher candidates enrolled at A University, B University, C University, and D University during the 2021 to 2022 academic year were included in the study. The participants were 161 females and 62 males. A theoretical model was constructed based on the findings of the literature review, and the relationships between these variables were tested using a structural equation model. In order to evaluate the fit of the data with the model, a series of goodness-of-fit indexes were calculated, including chi 2, RMSEA, CFI, GFI, and AGFI. The data were collected using the Critical Listening Attitude Scale, the Academic Listening Ability Scale, and the Metacognitive Listening Strategies Instrument. A correlation analysis and path analysis were conducted to examine the data using the SPSS v22 and AMOS v24 software packages, respectively. The findings indicate that metacognitive listening strategies are positively and significantly correlated with critical listening attitudes and academic listening skills. Nevertheless, the present study has demonstrated that metacognitive listening strategies are predictive of academic listening skills, and that this is mediated by critical listening attitudes. The results obtained in this study were discussed in the context of previous research, and accordingly, recommendations were made to practitioners, researchers, and policy makers working in this field.
Keywords: metacognitive listening strategies; listening attitudes; critical listening; structural equation modeling